Cross-Reference terhadap Bibel dalam The Holy Qur’an: Text, Translation and Commmentary Karya Abdullah Yusuf Ali - Nur Anis Rochmawati (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2021)
Many subjects mentioned in the Bible are found in the Qur’an. Based on the significant inconsistencies in the Bible and its internal contradiction with proven historical and scientific facts, Louay Fatoohi and Shetha al-Dargazelli declare their doubt about Bible’s reliability as a historical source. However, Abdullah Yusuf Ali has a different idea. He suggests that the Biblical material could be either true or false. This idea leads him to see the intertextual relationship between the Qur’an and the Bible in his The Holy Qur’an: Text, Translation, and Commentary. This article is an attempt to elaborate on Abdullah Yusuf Ali’s view on the Bible and to explore his strategies in citing the Bible as one of the sources of his interpretation. It employs the cross-reference method, as introduced by Edip Yuksel, to explore the citation of the Bible in understanding the Qur’an. With this method, this paper sketches and elaborates on the citations made by Abdullah Yusuf Ali in his The Holy Qur’an.